Micro-CT and histological examination of accessory canals in 34 equine cheek teeth - Korsós, Szabolcs A.; Staszyk, Carsten; Boone, Matthieu; Josipovic, Iván; Vogelsberg, Jörg; Vlaminck, Lieven (Frontiers in Veterinary Science, 2024)
Accessory canals and apical deltas haven been extensively studied iIn human dentistry,. Their clinical role as a difficult to clean reservoir for bacteria during endodontic treatments has been well described. Many papers describe in detail the pulp anatomy of equine dentition but little attention has been given to their apical ramifications. The goal of this paper is to describe the presence and anatomy of these accessory canals and apical deltas in healthy equine cheek teeth and discuss their possible relevance in the light of equine endodontics. To accomplish this, 15 maxillary and 19 mandibular healthy cheek teeth were collected ranging from Triadan 06s to 11s with eruption ages from 4 to 9 years. Their root anatomy was documented in detail based on micro computed tomography images. A subset of 3 teeth also underwent histological examination. Accessory canals were found in all but two teeth examined. Up to 44 accessory canals per tooth have been found with locations ranging from the root furcation down to the apex of the root and with highly variable diameters. Apical deltas in different stages of development were found in 84% of the roots. The presence of accessory canals identified on microCT images could be confirmed using histological examination although some of them were obliterated by reparative dentin. Accessory canals can be found in most equine cheek teeth and add complexity to their endodontic anatomy. This could have important implications for their treatment in case of pulp pathology. In humans, failure to remove bacterial biofilm from such canals has been associated with failure of endodontic treatment. Research on diseased equine teeth is required to gain a better understanding of their clinical relevance in horses.